2017
DOI: 10.1037/hea0000428
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a storybook targeting parental attitudes, intention, and self-efficacy to change their child’s oral health behavior.

Abstract: Objective: Methods for reducing dental disease have traditionally focused on health education rather than targeting psychosocial determinants of the core behaviors through behavior change strategies. This study tested a novel intervention in the form of a children's story (Kitten's First Tooth) embedded with behavior change techniques (Abraham & Michie, 2008) with the aim of investigating how effective the intervention was at improving parents' efficacy and intention to enact oral health behaviors for their ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Interventions that have manipulated mastery experience (i.e., prompting successful behaviour practice) and vicarious experience (i.e., observing a model performing the behaviour) have been shown to produce high levels of self‐efficacy, as well as providing feedback on past or others’ performance (Ashford et al ., ; Luszczynska & Schwarzer, ). Also, using storybook techniques that embed strategies that map onto parents’ self‐efficacy have been shown to improve parental self‐efficacy towards child toothbrushing behaviours (O'Malley et al ., ). In addition, given social support is important for parental health behaviours (Hamilton & White, , ) and has been shown to buffer the effect of low self‐efficacy (Hamilton, Warner, & Schwarzer, ; Zhou, Gan, Hamilton, & Schwarzer, ), providing support to parents (e.g., providing encouragement, giving information) may help to facilitate action.…”
Section: Discussionmentioning
confidence: 97%
“…Interventions that have manipulated mastery experience (i.e., prompting successful behaviour practice) and vicarious experience (i.e., observing a model performing the behaviour) have been shown to produce high levels of self‐efficacy, as well as providing feedback on past or others’ performance (Ashford et al ., ; Luszczynska & Schwarzer, ). Also, using storybook techniques that embed strategies that map onto parents’ self‐efficacy have been shown to improve parental self‐efficacy towards child toothbrushing behaviours (O'Malley et al ., ). In addition, given social support is important for parental health behaviours (Hamilton & White, , ) and has been shown to buffer the effect of low self‐efficacy (Hamilton, Warner, & Schwarzer, ; Zhou, Gan, Hamilton, & Schwarzer, ), providing support to parents (e.g., providing encouragement, giving information) may help to facilitate action.…”
Section: Discussionmentioning
confidence: 97%
“…The second strategy would be to explore use of storybooks to target parental attitudes towards childhood vaccination. This technique has been used with parental attitudes towards children’s oral health behavior and found to be effective [32]. The premise is that the story is written for children but subtly gets parents to think about their attitudes towards the subject.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a study of primary school children in Australia reported that higher parental self-efficacy was associated with more frequent tooth brushing by parent and child [18]. Intervention studies suggested that parents’ self-efficacy was modifiable: an intervention using a storybook that was embedded with behavioral change techniques showed that parental self-efficacy and intention to enact oral health behavior for their young children was significantly improved in England [19]. Similarly, four small 90-min group sessions that provided educational information, direct instruction, practice, and peer-to-peer problem solving improved parental self-efficacy for tooth brushing, and the proportion of parents who reported brushing their young children’s teeth twice per day increased significantly in the USA [20].…”
Section: Discussionmentioning
confidence: 99%